(untitled) (مجلة وقف في دراسات الاوقاف, 2026)
The General Purpose of the Scientific Article: The book aims to provide answers to important questions: 1. How did endowment projects transform into a soft power that managed to establish their position within the general civilizational context? This was achieved through the central What is Hidden by the Perpetual Charity (Articles and Research in Endowment) Book Series (12) Published by the Kuwait Awqaf Public foundation, Kuwait, 2020 CE Prepared by: Consultant Dr. Tariq bin Abdullah Kuwait Awqaf Public foundation, Kuwait 71 Issue No. Eight MUHARM 1445H / JULY 2023AD (Waqf) scientific peer-reviewed journal 5. A prevalent practice noted in various documents is the encouragement of fasting during Ramadan by endowers. This reflects a religious conviction that highlights the virtuous competition of philanthropists in giving and charity during the blessed month Ramadan. 6. The documents reveal a wealth of information about individuals, families, scientists, writers, places, terminology, social customs, administrative and financial organizations, and security, providing crucial insight for historians, genealogists, and researchers interested in the scientific movement in Najd and specifically Ushaiqer. 7. The documents shed light on various tools utilized in Ushaiqer, including measurement tools, currencies, agricultural and irrigation equipment, cooking utensils, offering a glimpse into the societal lifestyle of that era. 8. The documented endowments vary in size (large, medium, small) and type (date palms, houses, machinery), and they underscore the participation of all segments of society according to their financial capabilities. Concluding Remark on the Research: This research contributes to the revival of the scientific and endowment heritage of Ushaiqer, a town situated northwest of Riyadh. It served as the primary intellectual center in Najd during the 10th-12th centuries AH, laying the scientific groundwork for the subsequent intellectual revival in the Najd region.